Seagrass density correlates with burrow abundance and size in the Zebra Mantis Shrimp (Stomatopoda: Lysiosquillidae) - Nurdin Kadir, Nadiarti; Anugrah La Nafie, Yayu; Priosambodo, Dody (Revista de Biología Tropical, 2022)
Introduction: Mantis shrimps are ecologically and economically important organisms in marine ecosystems. However, there is still a lack of information about their habitat, in particular, their burrows. Objective: To analyze how dense and sparse mantis shrimp burrows differ in abundance, size, sediment grain size, and water quality. Methods: We counted burrows in 10 x 10 m2 random plots in sparse and dense seagrass (ten plots per density), around Barrang Lompo Island, South Sulawesi, Indonesia. Sampling took place at spring low tide from August to September 2017. Results: Two mantis shrimp species were observed: Lysiosquillina maculate and L. sulcata. Dense and sparse seagrass burrows did not differ in wall grain size or water parameters, both inside and outside of the burrows (P > 0.05). Similarly, there was no correlation between burrow depth and diameter in either dense (P > 0.05; r= 0.27) or sparse (P > 0.05; r= 0.33) seagrass. However, larger burrows tend to occur in denser beds, but there were more burrows in denser seagrass (t-test, P < 0.05). Conclusions: There seems to be a preference for dense seagrass beds, especially by larger mantis shrimps. The correlation between shrimp burrow abundance and seagrass density highlights the importance of conserving the quality as well as the extent of seagrass habitat.